Light-Mediated Signaling and Metabolic Changes Coordinate Stomatal Opening and Closure - Yang, Juan; Li, Chunlian; Kong, Dexin; Guo, Fangyan; Wei, Hongbin (Frontiers in Plant Science, 2020)
Stomata are valves on the leaf surface that control carbon dioxide (CO2) influx for photosynthesis and water loss by transpiration. Light is not only an energy source for photosynthesis but also an important signal regulating stomatal movement. Plants have evolved elaborate mechanisms to modulate stomatal aperture in response to changes in ambient light quantity and quality. Our knowledge concerning the effects of blue and red light signaling and light-induced guard cell (GC) metabolism on stomatal opening is accumulating. This review summarizes recent advances on the signaling components that lie between the perception of blue/red light and activation of the PM H+-ATPases, and on the negative regulation of stomatal opening by red light-activated phyB signaling and ultraviolet (UV-B and UV-A) irradiation. Besides, light-regulated GC-specific metabolic changes, mesophyll-derived sucrose and CO2 concentration within GCs also play dual roles in stomatal opening. Thus stomatal opening is tightly controlled by brake mechanisms in scenarios of strong solar irradiance, allowing plants to coordinate carbon gain and water loss. Knowledge on the mechanisms regulating the trade-off between stomatal opening and closure may have potential applications toward improving the water use efficiency (CO2 gain versus water loss) of crops.